2016
DOI: 10.1038/ijo.2016.178
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of motivation for food by neuromedin U in the paraventricular nucleus and the dorsal raphe nucleus

Abstract: BACKGROUNDMotivation for high-fat food is thought to contribute to excess caloric intake in obese individuals. A novel regulator of motivation for food may be Neuromedin U (NMU), a highly-conserved neuropeptide which influences food intake. Although these effects of NMU have primarily been attributed to signaling in the paraventricular nucleus of the hypothalamus (PVN), NMU has also been found in other brain regions involved in both feeding behavior and motivation. We investigate the effects of NMU on motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
(79 reference statements)
0
22
0
1
Order By: Relevance
“…Most NMU studies, including ours, have been performed secondarily to intracerebral or peripheral administrations of NMU or stable forms of NMU (7, 11, 15, 22, 29, 30). However, the physiology of NMU secretion in the plasma is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Most NMU studies, including ours, have been performed secondarily to intracerebral or peripheral administrations of NMU or stable forms of NMU (7, 11, 15, 22, 29, 30). However, the physiology of NMU secretion in the plasma is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…That is, knockdown of NMUR2 in the paraventricular nucleus of the hypothalamus potentiates binge‐type eating, increases consumption of a high‐fat diet, and stimulates weight gain . Recent studies have also shown that NMU administered to the paraventricular nucleus of the hypothalamus also decreases intake and motivation for high‐fat diet . Taken together, NMUR2 activation shows therapeutic promise for treating obesity.…”
Section: Introductionmentioning
confidence: 97%
“…19 Recent studies have also shown that NMU administered to the paraventricular nucleus of the hypothalamus also decreases intake 20 and motivation for highfat diet. 5 Taken together, NMUR2 activation shows therapeutic promise for treating obesity.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations